Exploring the Labyrinth Of Thought: Teachers' Perceptions of the Importance of Science Learning in Early Childhood Education - Sri Sukatmi; Tedy Andrian (JURNAL PENDIDIKAN USIA DINI, 2024)
This research aims to explore the understanding, planning, implementation, and evaluation of science learning carried out by early childhood education teachers, as well as identify the challenges faced and the solutions implemented. Using a qualitative approach, data was obtained through in-depth interviews with six teachers from various early childhood education institutions. Data analysis was carried out thematically by linking the research results to pedagogic theory and empirical context. The results of the study show that teachers have a diverse understanding of the concept of science, which is generally seen as a science to foster curiosity and critical thinking skills in children. In lesson planning, teachers use themes relevant to children's lives and develop exploration-based activities using simple tools and materials. The implementation of learning is carried out through hands-on experiments, demonstrations, and exploration-based projects designed to make science learning fun and meaningful. Evaluation of learning success focuses on children's enthusiasm, active participation, and understanding of science concepts. However, teachers face a variety of challenges, including limited tools and materials, limited learning time, and a variety of children's abilities. Creative solutions such as the use of local resources and additional motivation to children are often applied to overcome these obstacles. This research emphasizes the importance of science learning in early childhood education in supporting children's cognitive, social, and emotional development, as well as the need for institutional support in the form of training and the provision of resources to improve teaching effectiveness.